The Influence of Job Training And Job Placement on Work Motivation of The Support Departement At PT Adis Dimension Footwear Tangerang Regency - Amran, Amran; Soebadio, Bizzma Buana Amriki; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
The purpose of this study was to determine the influence of simultaneous training and job placement on the work motivation of the Support department at PT. Adis Dimension Footwear Balaraja-Tangerang.This study used a quantitative descriptive method, with a sample size of 78 respondents. Simple random sampling was used to determine the sample size. The Slovin formula was used to determine a representative sample size in quantitative research. Data analysis used multiple linear regression analysis with SPSS 26.The results of this study indicate that (1) partially, training significantly influences the work motivation of the Support department at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated t-value > t-table (4.514 > 1.992) and a significance value of 0.000, which is less than 0.05. Therefore, Ha is accepted and H0 is rejected. (2) partially, job placement significantly influences the work motivation of the Support department at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated t-value > t-table (2.223 > 1.992) and a significance value of 0.000, which is less than the 0.05 level. Therefore, Ha is accepted and H0 is rejected. (3) Simultaneously, training and job placement significantly influence work motivation in the Support department at PT. Adis Dimension Footwear Balaraja-Tangerang, as indicated by the calculated F-value > F-table (39.902 > 3.12) with a significance level of 0.000. Therefore, Ha is accepted and H0 is rejected.Based on the research results, it can be concluded that training and job placement, both partially and simultaneously, have a significant influence on work motivation in the Support department at PT. Adis Dimension Footwear Balaraja- Tangerang.